Ten-Year Legacy Effects of Three Eight-Month Exercise Training Programs on Cardiometabolic Health Parameters - Johnson, Johanna L.; Slentz, Cris A.; Ross, Leanna M.; Huffman, Kim M.; Kraus, William E. (Frontiers in Physiology, 2019)
Background: STRRIDE (Studies Targeting Risk Reduction Interventions through Defined Exercise) was an eight-month exercise study conducted from 1998-2003. Subjects were randomized to control or one of three exercise groups differing in intensity and amount. To determine if there were legacy effects, we invited 161 individuals who completed the intervention phase to return for a 10-year Reunion study. Methods: Subjects completed medical history and physical activity questionnaires. Height, body weight, blood pressure, waist circumference, and peak VO2 were measured. Fasting blood samples were analyzed for glucose, insulin and lipids. Of 161 original subjects, 153 were within 10 years of STRRIDE completion. Of these, 28 were lost to follow-up and 21 declined to participate in the Reunion study. Overall, 104 subjects (83% eligible) participated. Change over time was computed as the 10-year reunion value minus the pre-intervention value. Significant within group changes were calculated using two-tailed t-tests. ANCOVA determined differences among groups with pre-intervention values as covariates. Bonferroni corrections were applied to account for multiple comparisons. Results: Ten years after completing STRRIDE, there were a number of group-specific health and fitness legacy effects. Original participation in either the moderate intensity exercise or control group resulted in a 10.5% decrease in peak VO2 over the ensuing 10 years. Conversely, both vigorous intensity groups experienced only a 4.7% decrement in cardiorespiratory fitness over that time period. As compared to controls, all three exercise groups experienced smaller increases in waist circumference. Those who participated in moderate intensity exercise experienced the greatest 10-year reduction in fasting insulin. Compared to all other groups, the moderate intensity subjects had greater reductions in mean arterial pressure at the Reunion timepoint. Summary: Ten years after completing a randomized eight-month exercise training intervention, previously sedentary individuals exhibited group-specific differences consistent with an intervention-based legacy effect on cardiorespiratory fitness and cardiometabolic parameters. These findings highlight the critical need to better understand the sustained legacy health effects of exercise training interventions.